CONCLUSIONS AND SUGGESTIONS IMPORTANCE OF TURNOVER TAX REVENUES IN THE FORMATION OF BUDGET REVENUES (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The importance of turnover tax revenues in the formation of budget revenues is an important aspect of fiscal management. A sales tax, also known as a sales tax (VAT), is a consumption-based tax levied on the sale of goods and services. It plays a decisive role in the formation of state revenues and financing of state expenditures. Examines the importance of turnover tax revenues in budget planning and the general economy. It can examine the impact of turnover tax on government revenue, fiscal stability and economic stability. It can also examine the efficiency of collection and administration of turnover taxes, highlighting problems and potential solutions in optimizing revenue generation. It can also address the role of turnover tax in promoting fair taxation, reducing tax evasion and ensuring a more equitable distribution of the tax burden.